Snaking into the Gothic: Serpentine Sensuousness in Lewis and Coleridge - Jeremy Chow (Humanities, 2021)
This essay charts the ways late-eighteenth-century Gothic authors repurpose natural histories of snakes to explore how reptile-human encounters are harbingers of queer formations of gender, sexuality, and empire. By looking to M.G. Lewis’s novel The Monk (1796) and his understudied short story “The Anaconda” (1808), as well as S.T. Coleridge’s Christabel (1797–1800), I centre the last five years of the eighteenth century to apprehend the interwoven nature of Gothic prose, poetry, and popular natural histories as they pertain to reptile knowledge and representations. Whereas Lewis’s short story positions the orientalised anaconda to upheave notions of empire, gender, and romance, his novel invokes the snake to signal the effusion of graphic eroticisms. Coleridge, in turn, invokes the snake-human interspecies connection to imagine female, homoerotic possibilities and foreclosures. Plaiting eighteenth-century animal studies, queer studies, and Gothic studies, this essay offers a queer eco-Gothic reading of the violating, erotic powers of snakes in their placement alongside human interlocutors. I thus recalibrate eighteenth-century animal studies to focus not on warm-blooded mammals, but on cold-blooded reptiles and the erotic effusions they afford within the Gothic imaginary that repeatedly conjures them, as I show, with queer interspecies effects.